Base‐free Suzuki‐Miyaura Coupling of (Z)‐Trifluoromethyl Alkenyltriflates: An Efficient Approach to α‐Trifluoromethyl Arylenes. Issue 42 (16th November 2020) - Zhang, Chunxia; Li, Dong; Zhao, Yilong; Zhao, Jinfeng; Qu, Jingping; Zhou, Yuhan
Abstract: An exogenous base is generally necessary for the traditional palladium‐catalyzed Suzuki‐Miyaura coupling reactions. We report a direct palladium‐catalyzed base‐free Suzuki‐Miyaura coupling reaction of α ‐trifluoromethyl alkenyl triflates and aryl boric acids. Using Pd(OAc)2 (10 mol %) and PPh3 (40 mol %) as catalyst, this reaction proceeds smoothly without base or other additive. A variety of common functional groups, such as methyl, phenyl, naphthyl, fluoride, chloride, bromide, cyano, thienyl and alkyl, were well tolerated and a series of α ‐trifluoromethyl arylenes were obtained in 84 %–100 % yields. Abstract : A direct palladium‐catalyzed base‐free Suzuki‐Miyaura coupling reaction of α ‐trifluoromethyl alkenyl triflates and aryl boric acids was described and a series of α ‐trifluoromethyl arylenes were obtained in 84 %–100 % yields.